Características dentales, cefalométricas y antropométricas en pacientes con displasia ectodérmica hipohidrótica (2010)
ABSTRACT: The objective of this study was to describe the facial and cephalometric characteristics of 16 patients with hypohidrotic ectodermal dysplasia (HED) being treated at the College of Dentistry of the University of Antioquia and to clinically and radiographically determine which teeth were present or absent; the age of the patients ranged between 5 and 19 years. Hypohidrotic ectodermal dysplasia is a genetic syndrome that mainly affects the embryonic ectodermal originated tissues, it is manifested as a triad which includes: hypotricosis, hypohidrosis and hypodontia; it is present in one of every one hundred thousand born alive. Intraorally, a delay in tooth eruption and conoid shaped teeth are observed, affecting both jaws. Other characteristics are: prominent front and, sunken nasal bridge, retrusion of the maxilla and, protrusion of the mandible. Methods: an univariate descriptive analysis was done using frequency tables, descriptive measurements, average, bar and pie graphs for the qualitative variables and frequency histograms for the quantitative variables. The statistical analysis was done with the SPSS data base, version 15.0. Results and conclusions: the decreased anthropometric measurements were: facial width (85.5%), cutaneous mandibular height for the upper lip (75%) and total upper lip height (56.3%). The increased measurements were: upper face height (81.3%), external inter canthal distance (68.8%) and forehead width (50%). At the skeletal level the cephalometric measurements showed Class III malocclusions with hypoplastic maxillas (62.5%), retrusion (81.3%), mandibles with adequate size and position and concave profiles (75%). The most commonly absent teeth were: upper and lower lateral incisors, upper first bicuspids and lower central incisors.